Široká definice a typologie seniorského abusu: fenomén týrání, zneužívání, zanedbávání a dalšího nevhodného jednání a zacházení s muži a ženami ve vyšším věku (EAN) Metodika - Lorman, Jan (Masaryk University Press, 2023)
The aim of the methodology is to give an understanding of elder abuse, typologies, manifestations, risks of occurrence and procedures for detection and solution. The methodology helps those who regularly come into contact with older people to put knowledge about elder abuse into practice. This can be anyone who is not, or should not be, indifferent to seeing an older person treated inappropriately. The methodology is primarily intended for people working in support services, with recommendations for other relevant actors such as general practitioners and specialists, the police, the social services of local authorities, etc. However, it can also be used by interested members of the public and by non-profit organisations, which also have an essential role to play in dealing with this phenomenon. The procedures and recommendations presented here are based on the research activities of the RESTABUS project, which draw on the findings of other research teams from all over the world and from a wide range of scientific disciplines, as well as on many years of experience in working with older people.